2020
DOI: 10.4209/aaqr.2020.07.0475
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Particle Collection Behaviors and Electrohydrodynamics Flow Characteristics in Electrostatic Precipitators

Abstract: Electrostatic precipitators (ESPs) are widely used to eliminate particulate matter emissions from industrial sources. However, the complex electrohydrodynamics (EHD) flow in ESPs can cause controversial conclusions on particle collection. This paper established an ESP model with an additional source term added to the equation of gas momentum conservation. Correlations between particle motion behaviors and EHD flow characteristics were investigated regarding various discharge voltage, particle size, and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Particles are injected into the computational domain from the inlet surface, and the motions and charging process of particles were calculated once through the domain. Collection efficiency as a function of the particle diameter can be obtained by using Equation (23). Figure 10 shows the particle tracking pathlines with respect to residence time for the case of 1 mm wire diameter, 55 kV, and U in = 1 m/s in the 230 mm wide channel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particles are injected into the computational domain from the inlet surface, and the motions and charging process of particles were calculated once through the domain. Collection efficiency as a function of the particle diameter can be obtained by using Equation (23). Figure 10 shows the particle tracking pathlines with respect to residence time for the case of 1 mm wire diameter, 55 kV, and U in = 1 m/s in the 230 mm wide channel.…”
Section: Resultsmentioning
confidence: 99%
“…lection efficiency as a function of the particle diameter can be obtained by using Equation (23). Figure 10 shows the particle tracking pathlines with respect to residence time for the case of 1 mm wire diameter, 55 kV, and Uin = 1 m/s in the 230 mm wide channel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that collection efficiency is greatly improved. [1] It is based on increasing dust dust-collecting efficiency of an ESP. The collection efficiency of an ESP is affected by mud particles collected by the electrodes.…”
Section: Introductionmentioning
confidence: 99%